The Influence of Interest and Talent Guidance through Religious Activities on The Development of Soft Skill Potential among Santri - Gema Akbar Putra Pamungkas; Dhikrul Hakim; Siti Asiah (Indonesian Journal of Teacher Education, 2026)
This study aims to examine the implementation of interest and talent guidance through religious activities, the development of soft skill potential among santri, and the influence of such guidance on that development at the Bani Umar Putra Dormitory of the Darul Ulum Islamic Boarding School in Jombang. The study employs a quantitative approach using purposive sampling, supplemented by observation, interview, and documentation data to enrich the interpretation of statistical results. The study population consisted of 140 santri, with a sample of 35 first-year junior high school level (SLTP) students. Primary data collection was conducted using a Likert-scale questionnaire. Data analysis involved validity and reliability tests, percentage analysis, normality tests, and multiple linear regression using SPSS software. The results indicate that the santri's talent falls into the "good" category (80%), interest is "good" (79.89%), and soft skill potential is "good" (80.51%). The data followed a normal distribution, with Shapiro-Wilk significance values ??of 0.198 for talent (X1), 0.090 for interest (X2), and 0.147 for soft skill potential (Y). Multiple linear regression analysis yielded the equation Y = 0.216 + 1.284X1 + 0.289X2, with an F-value of 1858.206 and a significance level of 0.000 (p < 0.05); thus, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It is concluded that interest and talent guidance through religious activities has a positive and significant influence on the development of soft skill potential among santri, particularly regarding self-confidence, communication skills, leadership, teamwork, responsibility, and discipline.